Karakteristik Tempat Perindukan Nyamuk Culex Sp. di Sekitar Tempat Tinggal Penderita Filariasis Limfatik di Kabupaten Brebes Tahun 2020 - Oktafian, Mita; Siwiendrayanti, Arum (Indonesian Journal of Public Health and Nutrition, 2021)
Brebes Regency, Central Java Province, Indonesia, has experienced an increase in lymphatic filariasis cases every year. There are three districts with the highest cases, namely Ketanggungan Subdistrict, Bantarkawung Subdistrict and Paguyangan Subdistrict. Culex sp. mosquitoes is one of the vectors of lymphatic filariasis in Java, Indonesia. This study was conducted to obtain information about the characteristics of the breeding places for Culex sp. in the area where people with lymphatic filariasis live. The design of this research was descriptive quantitative research with a survey method. The population and samples were all lymphatic filariasis patients in the three districts that had the highest cases with a total of 15 patients. The research instrument used were observation sheets. The observed breeding places around the residence of lymphatic filariasis patients were puddles or stagnant water, river, and sewers with mostly on 0-200 meters from patient’s house. Puddle/stagnant water and sewers whose animal water absent were observed had larvae presence. The most preferred breeding place for mosquitoes in the research sites was uncovered sewers.